2023
DOI: 10.3390/aerospace10060544
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Research on Characteristics of Impulse Coupling and Plasma Plume Generated by Laser Irradiating Copper Target with Nanosecond Pulsed Laser Propulsion

Abstract: The ejection of the plasma plume produced by laser ablation is an important process for inducing mechanical effects. Therefore, in this paper, the characteristics of the plasma plume are investigated in order to analyze the impulse coupling mechanism with two laser spot diameters, 300 μm and 1100 μm, respectively. The impulse generated by laser irradiating the copper target was measured by the torsion pendulum, and the plasma plume was investigated using fast photography and optical emission spectroscopy. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…Comparison of experimental data on laser-ablative momentum coupling from the literature with 1D-FEM simulation results at the same laser parameters. While pure metals serve as a reference for Al[51] and Cu[52], results for alloys have been taken from[53] for comparison with Fe simulation results (30CrMnSiA steel) and Ti (TC4 alloy), respectively. Whereas the numerical values of the experimental data were provided alongside the paper in the case of[51], underlying numerical data have been extracted from the graphs of[52,53] usingWebPlotDigitizer 4.6 [54].…”
mentioning
confidence: 99%
“…Comparison of experimental data on laser-ablative momentum coupling from the literature with 1D-FEM simulation results at the same laser parameters. While pure metals serve as a reference for Al[51] and Cu[52], results for alloys have been taken from[53] for comparison with Fe simulation results (30CrMnSiA steel) and Ti (TC4 alloy), respectively. Whereas the numerical values of the experimental data were provided alongside the paper in the case of[51], underlying numerical data have been extracted from the graphs of[52,53] usingWebPlotDigitizer 4.6 [54].…”
mentioning
confidence: 99%
“…Thereby, it is used to describe the energy utilization efficiency of converting laser energy into the target momentum. Previous researches have shown that the impulse characteristics depended on laser parameters (wavelength, energy, pulse width, and spot size), ambient conditions (gas composition and pressure), target properties, etc [12][13][14][15][16]. Among these factors, laser wavelength has a significant effect on lasertarget coupling, ablation rate, penetration depth, plasma ignition threshold, and plasma absorption [17].…”
Section: Introductionmentioning
confidence: 99%